Comparison of the Effectiveness of Transactional Analysis Therapy and Acceptance and Commitment Therapy on Sexual Function, Body Image, and Self-Silencing in Overweight Infertile Women - Rafiepoor, Amin; Moghimi, Saranaz; Karfeh Raveshi, Fatemeh (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to compare the effectiveness of Transactional Analysis Therapy (TAT) and Acceptance and Commitment Therapy (ACT) in improving sexual function, body image, and self-silencing in overweight infertile women. A randomized controlled trial (RCT) was conducted with 45 overweight infertile women recruited from fertility clinics in Tehran. Participants were randomly assigned to three groups: TAT (n = 15), ACT (n = 15), and a control group (n = 15). Both experimental groups underwent 12 weekly therapy sessions, while the control group received no psychological intervention. The Female Sexual Function Index (FSFI), Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBSRQ-AS), and Silencing the Self Scale (STSS) were administered at pre-test, post-test, and three-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27. Both TAT and ACT significantly improved sexual function and body image while reducing self-silencing from pre-test to post-test (p < .001), with improvements largely maintained at follow-up. The ANOVA results confirmed significant time and group effects for all variables, and post-hoc comparisons showed that both interventions were superior to the control group. However, no significant differences were found between TAT and ACT in terms of their effectiveness (p > .05). These findings suggest that both therapies offer comparable psychological benefits for overweight infertile women. The results indicate that both TAT and ACT are effective interventions for addressing sexual dysfunction, body image dissatisfaction, and self-silencing in overweight infertile women. Given their comparable effectiveness, therapy selection should be tailored to individual preferences and treatment goals.